The Interesting Side of the Birth of a Demonstrator Mansur Samin in Ian Watt's Social Perspective - Moch. Fachrul Mustika; Jumiati Lanta; M. Nurzin R. Kasau (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2024)
The material object of this research is Mansur Samin's social criticism in his poem entitled "Pidato Seorang Demonstran". This poem is full of socio-political protests that discuss the situation experienced by the Indonesian people during the 1960s. The formal object of this poem uses a literary sociology approach adopted from Ian Waat's theory, which focuses on the societal aspects of literary works, considering them as the author's response to social reality. The findings produced in this study are that the poem "Pidato Seorang Demonstran" reflects the background of political change, economic instability, and dissatisfaction of the society at that time. The social criticism in this poem includes abuse of power, economic, political, and human rights issues. The critique addresses military repression, economic inequality, the behavior of political leaders, and human rights violations. The poem becomes a voice that reflects the socio-political conditions of Indonesia at that time and provides a perspective on the aspirations and discontent of the people.